2022
DOI: 10.3390/jcm11030859
|View full text |Cite
|
Sign up to set email alerts
|

Women in Advanced Reproductive Age: Are the Follicular Output Rate, the Follicle-Oocyte Index and the Ovarian Sensitivity Index Predictors of Live Birth in an IVF Cycle?

Abstract: (1) Background: Several researchers have investigated alternative markers related to ovarian responsiveness in order to better predict IVF outcomes, particularly in advanced reproductive-aged women. The follicular output rate (FORT), the follicle-oocyte index (FOI) and the ovarian sensitivity index (OSI) are among the most promising. However, these three metrics have not been investigated as independent predictors of live birth in women of advanced reproductive age; neither have they been compared to the two ‘… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…Higher FOI was associated with higher implantation rate and live birth rate after first fresh embryo transfer ( 19 ). However, similar results were not found in another cohort of women of advanced age with unexplained infertility ( 20 ). To date, evidence on the relationship between FOI index and successful pregnancy in IVF is sparse and lacks systematization.…”
Section: Introductionsupporting
confidence: 54%
See 4 more Smart Citations
“…Higher FOI was associated with higher implantation rate and live birth rate after first fresh embryo transfer ( 19 ). However, similar results were not found in another cohort of women of advanced age with unexplained infertility ( 20 ). To date, evidence on the relationship between FOI index and successful pregnancy in IVF is sparse and lacks systematization.…”
Section: Introductionsupporting
confidence: 54%
“…To our knowledge, only a few studies in the literature regarded the predictive value of FOI in IVF treatment, and the results were inconsistent ( 19 , 20 , 29 ). A retrospective analysis included 264 IVF cycles and found that higher FOI was associated with the higher implantation rate and live birth rate after first fresh embryo transfer ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations